Queering Azusa: Towards Pentecostal Fugitivity - Day, Keri (PentecoStudies, 2024)
How might a queer reading of the Azusa Street Revival of 1906 in Los Angeles, CA, help one engage with questions of anti-queer sentiment and practice, especially when assessing issues of gender and sexuality within contemporary Pentecostalisms? Drawing on my book Azusa Reimagined: A Radical Vision of Religious and Democratic Belonging, I suggest that Azusa can be interpreted in a queer register, which might assist Pentecostal communities when engaging with questions of gender and sexual difference. Specifically, I argue that the Azusa Street Revival is a queer theological resource, expanding how we understand queer religiosity itself and aiding contemporary Pentecostalisms when addressing questions of gender and sexual difference. To argue Azusa as a queer theological resource, I first briefly define what I mean by queer before offering a constructive queer interpretation of Azusa’s black religiosity. I then turn to historical snapshots of how Azusa operated outside of the constraints of gender performativity (to use feminist philosopher and gender theorist Judith Butler’s words), as this community often challenged the biological essentialisms and gender norms of its day. Finally, I offer one way that Azusa’s Pentecostal experiences might empower theology to be a "fugitive" discourse, on the run and taking flight from prevailing norms and rules that disallow and even punish queer identity and experience.